(untitled) (Agricultural Engineering, 2018)
The aim of the paper is to discuss the links between modern livestock production, including its techniques and concentration, with animal welfare requirements. Modern livestock production is related to modern facilities, precise livestock production, as well as intensive and high stocking density. At the same time, it requires providing the animals with minimal living conditions, i.e. the welfare set out in the relevant regulations. This in turn should guarantee a good quality of raw livestock materials and products.